Isolation and molecular detection of respiratory bacterial agents from buffalo reared in some selected areas of Bangladesh (Asian Journal of Medical and Biological Research, 2018)
In buffalo respiratory bacterial infection is very common which occurs sporadically or enzootically all over Bangladesh causing high economic loss. The study was performed with a view to proper control of respiratory bacterial infection in Buffalo. A total of 40 samples were collected on the basis of clinical signs. The samples were then subjected to isolation, identification and characterization of the bacterial agents using cultural, biochemical and molecular techniques. Antibiogram profiles of the isolated agents were studied by disc diffusion method. Pasteurella multocida, Staphylococcus aureus and E. coli were successfully isolated and identified from the collected samples. The isolated Pasteurella multocida produced small, round, opaque colonies on blood agar; Staphylococcus aureus produced golden yellow colony in mannitol salt agar; E. coli produced black color colonies with metallic sheen on EMB agar. Pasteurella multocida showed Gram negative, bipolar rods. Staphylococcus aureus showed Gram positive, cocci shaped and E. coli showed Gram negative, small rod shaped. On the basis of cultural and biochemical characteristics, among 40 nasal samples 5 were found to be positive for Pasteurella multocida, 4 for Staphylococcus aureus and 3 for E. coli. Pasteurella multocida was further confirmed by PCR where isolates showed positive band at 620 bp. The antibiogram study concluded that amoxicillin, gentamicin, & ciprofloxacin should be the first choice of treatment for respiratory bacterial infection caused by the isolated 3 bacteria.Asian J. Med. Biol. Res. December 2018, 4(4): 416-421